One-step in-situ reaction synthesis of TiC/graphene composite thin film for titanium foil surface reinforcement. (February 2019) - Luo, Bingwei; Zhou, Haitao; Liu, Dabo; Luo, Fei; Tian, Ye; Chen, Dongsheng; Wei, Wei
Abstract: TiC/graphene composite layer was successfully in-situ grown on the surface of Ti foil by a one-step plasma enhanced chemical vapor deposition (PECVD) method. The as-prepared sample was systematically characterized by X-ray diffraction (XRD), Raman spectrum, scanning electron microscopy (SEM) and Transmission electron microscopy (TEM). The results showed the composite layer was uniformly distributed on the surface of Ti foil with strong binding force. The surface hardness values of bare Ti foil and Ti/TiC/graphene composite were 204.84 HV and 641.18 HV, respectively, and the yield strength average values of annealed Ti and Ti/TiC/graphene were 137.3 MPa and 141 Mpa, respectively. The surface hardness of the TiC/graphene layer could be significantly increased twice as that of the bare Ti foil surface while maintained the strength stability. Nanoindentor results showed the significantly improved surface hardness could be attributed to the TiC layers. This study provides a facile strategy for surface reinforcement of Ti and its alloys, showing great potential for future application. Highlights: TiC/graphene composite layer was prepared by one-step chemical vapor deposition method on Ti foil. The TiC/graphene layer could significantly enhance the mechanical property of Ti foil. The surface reinforcement of Ti foil could be attributed to the TiC layers.